Association between coenzyme Q 10-related genetic polymorphisms and statin-associated myotoxicity in Korean stroke patients - Park, Yoon-A; Chang, Yoonkyung; Lee, Da Hoon; Kim, Jung Sun; Park, Minju; Choi, Seo-A; Song, Tae-Jin; Gwak, Hye Sun (Frontiers in Pharmacology, 2024)
Introduction: The purpose of this study is to identify the relationship between coenzyme Q 10 (CoQ10)-related gene polymorphisms and statin-related myotoxicity (SRM).Methods: We retrospectively analyzed prospectively collected samples from February to May 2021. To investigate the association between CoQ10-related genetic factors and SRM, we selected 37 single nucleotide polymorphisms from five genes (COQ2, COQ3, COQ5, COQ6, and COQ7). The odds ratio (OR) and adjusted OR with 95% confidence intervals (CI) were calculated for univariate and multivariable logistic regression analyses, respectively.Results: A total of 688 stroke patients were included in the analysis, including 56 SRM cases. In the multivariable analysis, two models were constructed using demographic factors only in model I, and demographic and genetic factors in model II. Compared to other statins, atorvastatin decreased the SRM risk whereas ezetimibe use increased the SRM risk in model I and model II. Patients with COQ2 rs4693075 G allele, COQ3 rs11548336 TT genotype, and COQ5 rs10849757 A allele had a 2.9-fold (95 % CI: 1.6-5.3), 1.9-fold (95 % CI: 1.1-3.5), and 3.3fold (95 % CI: 1.5-8.3) higher risk of SRM, respectively.Conclusion: This study could be utilized to develop a personalized medicine strategy in patients treated with statins.